Los hititas en Anatolia septentrional durante la primera mitad del s. XIII a.C. (II). La organización político-administrativa de una región conflictiva del reino de Hatti - González Salazar, Juan Manuel (Gerión. Revista de Historia Antigua, 2001)
Hattusili III, Great King of Hatti in the middle of the thirteenth century B.C., took an active part in the Hittite imperial organization. In particular, this monarch attempted to organize a complex and sophisticated system of territorial administration of the frontiers. In the Hittite-Gasgean border area, for example, regional control became of vital interest. The characteristic features of the peripheral policy towards the Gasgean population groups in the northern zone of Hatti may be illustrated by two hittite documents: a text on the reorganization of cults (KBo XII 53+KUB XLVIII 105) and a royal edict (KUB XXI 29+duplics.). Hattusili III tried to maintain his political authority over this widely extended limes by means of an administrative and military framework. In general, the hittite king achieved a long period of imperial stability before the destruction of the Hatti Kingdom.